A man of the people - Achebe, Chinua; Penguin Books (London : Penguin Books, 2001)
A schoolteacher risks his life to oppose a corrupt politician in this novel by noted twentieth-century Nigerian author Chinua Achebe, in which he explores the political state of his home country preceding the 1966 coup.
Adult
Keywords: Politicians -- Nigeria -- Fiction; Political fiction; Satire; Nigeria -- Politics and government -- Fiction